What is factor contributing to medical student learning anxiety during COVID-19 pandemic? A systematic review - Amin Aji Budiman; Retno Lestari; Laily Yuliatun (International Journal of Public Health Science (IJPHS), 2021)
Changes in education aspects increase the risks for mental and emotional disorders on students during the COVID-19 pandemic. This article aimed to discover the factors are contributing to medical students' learning anxiety during the COVID-19. A systematic review was written based on scientific article identification on three databases of Science Direct, PubMed NCBI, and EBSCO using terms of anxiety, factors, students, and COVID-19. The authors selected and analyzed using PRISMA based on predetermined inclusion and exclusion criteria. The studies obtain from several electronic databases revealed 519 research articles and a total of 20 articles to be analyzed. The internal factor of student anxiety during COVID-19 pandemic is age, gender, and lack of knowledge. The external factor is high academic loads with online learning methods, area restrictions/lockdown, physical activities, and socio-economic status changes. Knowing the factors that affect medical student anxiety during the pandemic could prevent further mental and emotional disorders and achieve optimal health.